Veterinary antibiotics influence trigonelline biosynthesis and plant growth in Arachis hypogaea L. (3rd April 2017) - Devireddy, Amith R.; Inupakutika, Madhuri A.; Willmon, David; Kakarla, Prathusha; Puppala, Naveen; Cho, Youngkoo
ABSTRACT: Antibiotics from various sources such as livestock waste are being accumulated in the soil. The excessive uptake of antimicrobial agents by plants has been a major concern as it is currently unknown how plants respond to the presence of antibiotics in agricultural lands. The objectives were to analyze the alteration of trigonelline (TRG) biosynthesized by plants in response to various antibiotic stresses and to evaluate the ability of peanut (Arachis hypogaea L.) plants to resist the deleterious impacts of antibiotic uptake. Three veterinary antibiotics used in this study were tetracycline, streptomycin sulfate, and chloramphenicol in the concentrations of 2.5 and 5 mg L −1 . Mean TRG amounts were 53.4 ± 1.6 and 59.9 ± 1.1 μg·g −1 dry weight (DW) in Spanish as treated with growth chloramphenicol and streptomycin at 2.5 mg·L −1, respectively, and were significantly (p ≤ .05) different compared to the control (40.4 ± 1.6 μg·g −1 DW) of Spanish. Spanish genotype treated with chloramphenicol at 5 mg·L −1 had a mean TRG amount of 41.0 ± 1.0 μg·g −1 DW and improved yield, with the average pod number of 29.6 ± 7.6 and pod weight of 20.1 ± 6.1 g. TRG was continuously biosynthesized and increased under antibiotic stress up to 12.7% at full pod (R4 growth stage) and 139.1% at beginning maturity (R7), but declined 20.2% at the harvest stage (R8) in all combined genotypes when compared with TRG amounts (21.7 ± 0.6 μg·g −1 DW) at the flowering R1 stage.